Biomass Distribution of Cajuput Stand in Central Kalimantan Swamp Forest - Alpian; Tiberius Agus Prayitno; Johanes Pramana Gentur Sutapa; Budiadi (Jurnal Manajemen Hutan Tropika, 2013)
In Central Kalimantan, cajuput (Melaleuca cajuputi subsp. cumingiana) mostly can be found in the riptide swamp area. The present research was intended to determine the distribution of biomass based on the part of tree, position to the ground surface, growing stage, and allometric equation models to estimate the prospective of biomass in 2 different locations (A and B). The A and B locations were characterized by type B riptide peat swamp forest (high tide effected with peat thickness of 51-100 cm) and type C riptide peat swamp forest (tide unaffected shallow soil of < 50 cm with peat thickness of 101-200 cm), respectively. The distribution of cajuput biomass based on the part of tree, position to the ground surface, and growing stage in both locations indicated a similar pattern. Stem contained the highest biomass followed successively by that of root, branch, leave, fruit, and flower. Biomass above the ground was also higher than that of below the ground. Furthermore, biomass content of poles was the highest, followed successively by that of sapling, tree, and seedling. Allometric equation models used to estimate biomass of the A location in the state of green, air dry, and oven dry were 0.335D2,35, 0.143D2,42, and 0.128D2,41, respectively. While those in the B location for green, air dry, and oven dry state were 0.279D2,48, 0.127D2,58, and 0.114D2,56, respectively. The potential of biomass in the A and B location were 144,100 and 127,212 ton ha-1, respectively.